Thermal signature of ion intercalation and surface redox reactions mechanisms in model pseudocapacitive electrodes. (1st June 2019) - Munteshari, Obaidallah; Lau, Jonathan; Likitchatchawankun, Ampol; Mei, Bing-Ang; Choi, Christopher S.; Butts, Danielle; Dunn, Bruce S.; Pilon, Laurent
Abstract: This study aims to investigate the thermal signature associated with the charge storage mechanisms in hybrid supercapacitors using in operando calorimetry under constant current cycling. The hybrid supercapacitors consisted of highly porous pseudocapacitive electrode and activated carbon (AC) electrode with either organic or aqueous electrolytes. Pseudocapacitive electrodes made of either molybdenum dioxide on reduced graphene oxide (MoO2 -rGO) or manganese dioxide on graphene (MnO2 -G) were synthesized to investigate heat generation associated with reversible redox reactions involving ion intercalation or fast surface redox reactions, respectively. Here, MoO2 -rGO served as the negative electrode against activated carbon electrode in 1 M LiClO4 in EC:DMC. In addition, electrolyte consisting of 1 M TBABF4 in EC:DMC was also used as a reference to suppress redox reactions and intercalation due to its large ionic size. On the other hand, mesoporous MnO2 -G electrode served as the positive electrode also against activated carbon electrode but in 0.5 M aqueous Na2 SO4 . First, a data analysis procedure was developed to distinguish between irreversible and reversible heat generation rates and to isolate Joule heating from the measured instantaneous heat generation rate at each electrode. In the AC electrodes, the irreversible heat generation rate was due to resistive losses (i.e., Joule heating) while the reversible heat generation was due to ion adsorption/desorption at the electrolyte/electrode interface. By contrast, irreversible heat generation rate in the pseudocapacitive electrodes exceeded Joule heating. This was attributed to irreversible heat generation associated with redox reactions, polarization heating, and hysteresis in EDL formation and dissolution. Finally, MoO2 -rGO negative electrode in LiClO4 featured endothermic reversible heat generation during charging due to Li + intercalation. Similarly, MnO2 -G positive electrode in Na2 SO4 featured endothermic heat generation during charging due to non-spontaneous surface redox reactions.